Phosphate price fluctuations and economic growth in Morocco: An ARDL-bounds approach - Kharibouch, Mehdi; Aissaoui, Zineb El; Dkhissi, Atman; Ghrabli, Youssef El (Asian Journal of Economic Modelling, 2025)
This research examined the relationship between international phosphate price volatility and economic growth in Morocco for the 1994-2020 period, using the Autoregressive Distributed Lag (ARDL) bounds testing approach to capture the short-run and long-run dynamics. The data used is annual in frequency and includes yearly time series of several key macroeconomic indicators, including nominal GDP, phosphate prices, CO2 emissions, fertilizer consumption, gross fixed capital formation, and unemployment. The study identified that phosphate price changes significantly affect Morocco’s short-run economic growth but have no statistically significant long-run impact on GDP. The increase of phosphate prices in the short run results in higher export revenues, but long-lasting price volatility limits economic diversification and environmentally sustainable options. Several structural inefficiencies were also found in Morocco’s economy, including the limited effect of capital allocation and high levels of unemployment that restrict sustainable growth. The study identified several key aspects that should be considered by Morocco as it looks to reduce its dependency on the phosphate sector, including economic diversification with a commitment to sustainable resource management across the economy, such as the use of human capital investments, green technologies, infrastructure investments, and appropriate changes to governance and policy. The study highlights the literature contributions of Morocco as an exceptional specific case, being the number one country for phosphate with a highly developed phosphate sector, and emphasizes that sustainable resource expenditure and volatility, drawn from effective policy responses to resource price volatility, are needed to support sustained human development.